Autoantibodies to Cytosolic 5′-Nucleotidase 1A in Primary Sjögren’s Syndrome and Systemic Lupus Erythematosus - Rietveld, Anke; van den Hoogen, Luuk L.; Bizzaro, Nicola; Blokland, Sofie L. M.; Dähnrich, Cornelia; Gottenberg, Jacques-Eric; Houen, Gunnar; Johannsen, Nora; Mandl, Thomas; Meyer, Alain; Nielsen, Christoffer T.; Olsson, Peter; et al. (Frontiers in Immunology, 2018)
Autoantibodies to cytosolic 5’-nucleotidase 1A (cN-1A; NT5C1A) have a high specificity differentiating sporadic inclusion body myositis from polymyositis and dermatomyositis. In primary Sjögren’s syndrome (pSS) and systemic lupus erythematosus (SLE) anti-cN-1A autoantibodies can be detected as well. However, various frequencies of anti-cN-1A reactivity have been reported in SLE and pSS, which may at least in part be explained by the different assays used. Here, we determined the occurrence of anti-cN-1A reactivity in a large number of patients with pSS and SLE using one standardized ELISA. Sera from pSS (n = 193) and SLE patients (n = 252) were collected in five European centers. Anti-cN-1A, anti-Ro52, anti-nucleosome and anti-dsDNA reactivities were tested by ELISA (Euroimmun AG) in a single laboratory. Correlations of anti-cN-1A reactivity with demographic data and clinical data (duration of disease at the moment of serum sampling, autoimmune co-morbidity and presence of muscular symptoms) were analyzed using SPSS software. Anti-cN-1A autoantibodies were found on average in 12% of pSS patients, with varying frequencies among the different cohorts (range: 7% - 19%). In SLE patients, the anti-cN-1A positivity on average was 10% (range: 6% - 21%). No relationship was found between anti-cN-1A reactivity and the presence or absence of anti-Ro52, anti-nucleosome and anti-dsDNA reactivity in both pSS and SLE. No relationship between anti-cN-1A reactivity and duration of disease at the moment of serum sampling and the duration of serum storage was observed. The frequency of muscular symptoms or viral infections did not differ between anti-cN-1A-positive and –negative patients. In both disease groups anti-cN-1A-positive patients suffered more often from other autoimmune diseases than the anti-cN-1A-negative patients (15% versus 5% (p = 0.05) in pSS, 50% versus 30% (p = 0.02) in SLE). Our results confirm the relatively frequent occurrence of anti-cN-1A in pSS and SLE and the variation in anti-cN-1A reactivity between independent groups of these patients. The explanation for this variation remains elusive. The correlation between anti-cN-1A reactivity and polyautoimmunity should be evaluated in future studies. We conclude that anti-cN-1A should be classified as a myositis-associated-, not as a myositis-specific-autoantibody based on its frequent presence in pSS and SLE.